Motivating Bureaucrats through Social Recognition: External Validity — A Tale of Two States - Varun Gauri; Julian C. Jamison; Nina Mazar; Owen Ozier (Institute of Labor Economics (IZA), 2019)
Bureaucratic performance is a crucial determinant of economic growth, but little real-world evidence exists on how to improve it, especially in resource-constrained settings. We conducted a field experiment of a social recognition intervention to improve record keeping in health facilities in two Nigerian states, replicating the intervention - implemented by a single organization - on bureaucrats performing identical tasks. Social recognition improved performance in one state but had no effect in the other, highlighting both the potential benefits and also the sometimes-limited generalizability of behavioral interventions. Furthermore, differences in facility-level observables did not explain cross-state differences in impacts, suggesting that it may often be difficult to predict external validity.
Keywords: C93; D73; D91; I18; L38; O35; 330; RCT; external validity; bureaucracy; behavioral insights; nudges; healthcare